Afterword on Geisterspiele - Bookchin, Natalie (Cinémas, 2024)
A reflection on making public art in private space during a lockdown, on intimacy during a time of distance and separation, on loneliness and connection, the Internet, uprisings and insurrections, walls and bodies breached, an interstitial space, between before and after.